Penggunaan Media Papan Pintar Untuk Meningkatkan Kemampuan Numerasi Anak Usia Dini Dalam Mengenal Lambang Bilangan 1-5 - Imas Basmiati; Tanto Aljauharie Tantowie; Desi Suryani (CV. Biha Cendekia, 2025)
This study aims to improve early childhood numeracy skills in recognizing number symbols 1-5 using smart board media. The research method used is Classroom Action Research (CAR) carried out in two cycles. The subjects of the study were children aged 4-5 years at PAUD Kober Assulha, totaling 14 children. Data were collected through observation and numeracy ability tests. The results of the study showed that the smart board was effective in enhancing children's understanding of number symbols 1-5. Children who reached the